Aspects of the design of the automated system for code generation of electrical items of technological equipment - Erokhin V.V.; Eliseeva E.V. (Научно-технический вестник Брянского государственного университета)
The article presents the aspects of designing an automated system for generating codes for electrical elements of process equipment using CASE-means. We propose our own technology of iterative development of such systems. The proposed methodology uses the tool to develop the ERwin Data Modeler databases of Computer Associates and the author's tool for the automatic generation of ERwin Class Builder code. The implemented design tool is a superstructure over the ERwin Data Modeler from Computer Associates, which extends its functionality. ERwin Data Modeler works with logical and physical data models and allows you to generate a description of the database and ddl-scripts.